(untitled) (Archives of Mechanics - Test, 2001)
A straightforward and complete description of all possible invariant linear decompositions of the space of Hooke’s tensors has been given in Part I, [1]. In this Part II we demonstrate various elaborations and consequences of these decompositions. This gives a qualitative description of the anisotropy of Hooke’s tensors. In particular, we demonstrate examples A through G, not only important but also astonishing. When reference is made to the formulae in [1], we shall add "Part I" to the number. The notions and notations are the same (see Appendices 1, 2 in [1]).